Malaysia, Indonesia and Thailand trends on food security research: a bibliometric analysis from 2003 to 2022 - Abdul Aziz, Nor Azni; Abdullah, Amini Amir; Abdul Wahab, Mat Azeli (Clm Publishing Resources, 2024)
Food security encompasses the availability, accessibility, utilization and stability of food sources for all. The objective of this paper is to explore the trend of publications on food security and to identify selected topics of publications on food insecurity in Malaysia, Indonesia and Thailand within 2003 to 2022. The method of this study was used bibliometric analysis on scientific publications through Scopus databased. The findings indicated that publications volume of food security on Malaysia, Indonesia and Thailand have significantly increased within last ten years starting from 2013 to 2020. Based on subject area, the publications of food security on these three Asian countries focuses more on the subject of agriculture, environmental, social science, earth & planet and the rest. The selected topics of publications of food insecurity on Malaysia was about health issue, household and elderly; Indonesia was about rural areas issue, rice production, urban areas issue, household issue, fisherman issue and coping strategies; Thailand was about household issue and rice production.